The influences of the type of information on the purchase intention and performance expectation of residential real estate properties - Dalbosco, Francieli Vargas; Lantelme, Elvira Maria Vieira; Rech, Eduardo (Ambiente Construído, 2021)
During the Purchase Decision Process (PDP), consumers use limited information to evaluate the value of an asset, considering that they do not have access to complete and adequate information, lack of knowledge and experience. Technical information about building performance can be used as differential attributes in the PDP. This research seeks to analyze the influence of technical information on the purchase intention and performance expectations of residential real estate consumers. Two studies were conducted, with different but complementary characteristics, the first one being exploratory and qualitative and the second one being experimental and quantitative. The results showed that information, regardless of its content and format, has a significant impact both on purchase intention and performance expectation when provided to the consumer during the purchasing process. However, the information content and format as used in the advertisements developed for this study’s experiment showed no significant differences in the variables analyzed. The main contribution of this work is to provide subsidies to improve the adaptation of real estate marketing advertisements and guarantee better and qualified information to consumers.